(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Carbapenems have been used as the last resort antimicrobials in the treatment of serious infections caused by gram negative bacteria. The rate of carbapenem resistance in non-glucose fermenting gram negative bacilli has been gradually increasing worldwide over last 10 years. These organisms can also cause life threating infections which are difficult to treat.Aim: This study was conducted to identify phenotypically for the presence of Carbapenemase production in glucose non-fermenting bacilli. Materials and methods: Among 200 Imipenem resistant isolates, 62 imipenem resistant samples showed glucose non-fermenting bacilli. All the isolates were tested for anti-microbial susceptibility (HI-Media Mumbai) by Kirby-Bauer disk diffusion method on Muller-Hinton agar. Carbapenemase production was detected by Modified-Hodge test, Combined Disc test, and AmpC Disc test phenotypically. Results. Out of 62 imipenem resistant isolates of glucose non-fermenting bacilli, 49 isolates were Pseudomonas spp. and 13 isolates were Acinetobacter spp.. Out of 62 , 13 were MHT positive, 36 were CDT positive and 14 were AmpC positive, 16 were Multiple enzyme producers, 17 were Non-Enzyme producers. Conclusion: Carbapenem resistance rate was more in Acinetobacter spp. than Pseudomas spp.. Our study has implicated the severity of carbapenem resistant non-fermenters, which are effecting the infection control activities among hospital setup.